2017
DOI: 10.1515/opag-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

From lab to life: Making storable orange-fleshed sweetpotato purée a commercial reality

Abstract: Open Agriculture. 2017; 2: 148-154 IntroductionThere is increasing interest in developing agro-industries in Sub-Saharan Africa (SSA) to expand agriculture's key role in poverty reduction (UNIDO 2009). In part, this recognizes the rapid rate of urbanization in the continent (Jedwab et al. 2014), with greater proportions of the population purchasing rather than growing their own food. Moreover, urban consumers often opt for foods in "convenient" processed forms, which can be consumed immediately or require redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Research efforts to date have successfully demonstrated in Rwanda that steamed and mashed OFSP (purée) can replace significant percentages (35–50%) of wheat flour in baked products ( Ndirigwe et al, 2015 ). A four month shelf-storable (using locally available preservatives), vacuum-packed purée that is less expensive than wheat flour has been developed that should facilitate adoption by the processing industry and is currently being tested with a purée factory in Kenya ( Bocher et al, in press ). Since many countries import significant amounts of wheat flour, OFSP purée substitution appeals to farmers, processors, and policy makers.…”
Section: Phase 3: the Stars Align (2010–2016)mentioning
confidence: 99%
“…Research efforts to date have successfully demonstrated in Rwanda that steamed and mashed OFSP (purée) can replace significant percentages (35–50%) of wheat flour in baked products ( Ndirigwe et al, 2015 ). A four month shelf-storable (using locally available preservatives), vacuum-packed purée that is less expensive than wheat flour has been developed that should facilitate adoption by the processing industry and is currently being tested with a purée factory in Kenya ( Bocher et al, in press ). Since many countries import significant amounts of wheat flour, OFSP purée substitution appeals to farmers, processors, and policy makers.…”
Section: Phase 3: the Stars Align (2010–2016)mentioning
confidence: 99%
“…Sweetpotato is consumed after steaming, boiling, frying or roasting (Odora et al ., 2000). Other products include puree, dried chips and chunks, flour, pastries and confectionery (Nakanyike, 2014; Abong et al ., 2016; Bocher et al ., 2017). Per capita annual consumption is estimated at 95 kg (Abong et al ., 2016) with perceived increased demand (Kyalo et al ., 2014; Okonya & Kroschel, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, incorporating the OFSP puree in foods is highly desirable and this ideology has been adapted in this research by incorporating various levels of OFSP puree in the wheat bread. Several bakeries and supermarkets in Kenya, Rwanda, Malawi, and Mozambique are exploring the commercial success of such food products (Bocher et al., 2017). Breads with 10% OFSP flour contain 0.04 µg/100 g of βC in the crumb and 0.05 µg/100 g in the crust that are equivalent of 3.9 and 5.4 RAE/100 g from crumb and crust, respectively (Muzhingi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%